DEHKANCHILIK CULTURE: TRADITIONALIST AND PAINTING-RUSUMLAR - Valikhonova Gulnorakhon Komiljonovna; Artikova Oltinoy; Akhmedov Komiljon (American Journals Publishing, 2024)
In this article, the author talks about the farming culture of the Uzbek people and the rituals that embody the unique thinking of the people in its development. Issues such as the deep historical roots of customs and rituals related to farming traditions, as well as the fact that they are closely related to religious views, are analyzed on the basis of historical sources.
Keywords: Agriculture, farmer, culture, tradition, ritual, calendar, heritage, farm, dervish, Bobodehkan, Khizrbuva.